Strategies of Teachers in Developing an Islamic Religious Education Curriculum - Resta Desty ladina Resta; Mohamad Erihadiana Erihadiana (KEDJATI Journal of Islamic Civilization, 2024)
In the current era, the teacher's role in developing a learning curriculum that suits needs is urgent. Teachers are required to empower various digital platforms such as learning applications, websites, and other online resources to make learning more exciting and facilitate students' accessibility. This research aimed to investigate teachers' strategies for increasing the Islamic religious education (PAI in Indonesian) curriculum. This study used literature reviews from various sources related to this topic. The results show that the teacher's strategies in curriculum development may vary according to the centralized, decentralized, or central-decentralized management approach. Teachers were also essential as implementers, adapters, developers, and researchers. Besides, teachers were not only asked to transfer knowledge but also responsible for conducting other crucial values through reciprocal interaction, which was the primary key in the learning process. It means that teachers guided students to get what pupils needed. Thus, this article provides an alternative model for teachers in developing and implementing the PAI curriculum to achieve educational goals.